Overcoming the Innovator’s Dilemma in Disruptive Process Innovation Through Subject Orientation - Fleischmann, Albert; Schmidt, Werner; Stary, Christian (Human-Computer Interaction. User Interface Design, Development and Multimodality, 2017)
Once digital technologies trigger business process management and change, organizations are challenged to (re)position their products and services. Thereby, creating disruptions could help overcoming the threat of being blindsided by novel developments. We consider Subject-oriented Business Process Management being capable to create socially acceptable organizational disruption through process modelling and explorative execution. S-BPM capabilities adjust changes in customer, product and organizational management through its unifying communication perspective. In this contribution, we report on creating disruptive innovation starting with subject-oriented re-design of work and production processes. The presented case, a large transformation process of an automotive company reveals that this type of disruptiveness enables an integrative perspective on existing work procedure in an aligned, since synchronized way. Hence, we can conclude that a starting point for innovation is grasping the collaborative nature of existing processes rather re-establishing functional positions and procedures.